Mercenaries in British and American literature, 1790-1830 : writing, fighting, and marrying for money - Simpson, Erik, 1972- (Edinburgh studies in transatlantic literatures., 2010)
In Mercenaries in British and American Literature, 1790-1830, Erik Simpson proposes the mercenary as a meeting point of psychological, national, and ideological issues that connected the severed nations of Britain and America following the American Revolution. When writers treat the figure of the mercenary in literary works, the general issues of incentive, independence, and national service become intertwined with two of the well-known social developments of the period: an increased ability of young people to choose their spouses and the shift from patronage to commercial, market-based support of authorship. While the slave, a traditional focus of transatlantic studies, troubles the rhetoric of liberty through a lack of autonomy and consent, the mercenary raises questions about liberty by embodying its excess. Simpson argues that the mercenary of popular imagination takes monstrous advantage of modern freedoms by contracting away the ostensibly natural and foundational bonds of civil society. Substantial primary research underpins an argument with suggestive metaphorical and symbolic implications traced through a range of writing by Charles Brockden Brown, Charlotte Smith, Walter Scott, Lord Byron, and James Fenimore Cooper. These writers present mercenary action with unusual complexity and self-awareness, reaching beyond propaganda to explore the problematic nature of the mercenary at the nexus of fighting, writing, and marrying for money.